Bilateral ptosis as a presenting feature of primary hypertrophic osteoarthropathy (pachydermoperiostosis): a case report - S. El Aoud; F. Frikha; M. Snoussi; R. Ben Salah; Z. Bahloul (PAGEPress Publications, 2014)
Pachydermoperiostosis is a rare hereditary disorder, which affects both bones and skin. It is characterized by a combination of dermatologic changes (pachydermia or thickening of the skin) and rheumatologic manifestations (periostosis and finger clubbing). Eyelid ptosis which is caused by thickened eyelids (blepharoptosis) is a less common symptom. We report the case of a patient with a complete form of pachydermoperiostosis with bilateral ptosis as presenting feature.